Does the Integrated Management of Childhood Illness cost more than routine care? Results from the United Republic of Tanzania - Taghreed Adam; Fatuma Manzi; Joanna Armstrong Schellenberg; Leslie Mgalula; Don de Savigny; David B. Evans
OBJECTIVE: The Integrated Management of Childhood Illness (IMCI) strategy is designed to address the five leading causes of childhood mortality, which together account for 70% of the 10 million deaths occurring among children worldwide annually. Although IMCI is associated with improved quality of care, which is a key determinant of better health outcomes, it has not yet been widely adopted, partly because it is assumed to be more expensive than routine care. Here we report the cost of IMCI compared with routine care in four districts in the United Republic of Tanzania. METHODS: Total district costs of child care were estimated from the societal perspective as the sum of child health-care costs incurred in a district at the household level, primary health-facility level and hospital level. We also included administrative and support costs incurred by national and district administrations. The incremental cost of IMCI is the difference in costs of child health-care between districts with and without IMCI, after standardization for population size. FINDINGS: The annual cost per child of caring for children less than five years old in districts with IMCI was US$ 11.19, 44% lower than the cost in the districts without IMCI (US$ 16.09). Much of the difference was due to higher rates of hospitalization of children less than 5 years old in the districts without IMCI. Not all of this difference can be attributed to IMCI but even when differences in hospitalization rates are excluded, the cost per child was still 6% lower in IMCI districts. CONCLUSION:IMCI was not associated with higher costs than routine child health-care in the four study districts in the United Republic of Tanzania. Given the evidence of improved quality of care in the IMCI districts, the results suggest that cost should not be a barrier to the adoption and scaling up of IMCI.